Attitudes toward people with disabilities in a sample of students of high school of Lima - Domínguez Lara, Sergio Alexis (2013)
Objective: To determine if there are differences in attitudes towards people with disabilities in a sample of high school students in Lima, considering variables such as sex, contact with people with disabilities and type of school. Method: Design ex post facto retrospective and descriptive-comparative. Were evaluated 432 students of high school from state and private schools of Lima, 237 males (50.9%) and 195 women (45.1%). Was used the Scale of Attitudes toward Individuals with Disability. Results: We report significant differences between men and women in relation to the scales Recognition/Denial of Rights (t(430)= -3.111; p< .01; d de Cohen =.30) and Personal Implication (t(430)= -5.438; p< .001; d de Cohen=.53) in favor of women; in relation to the type of school, in Valuing Capabilities and Limitations (t(430)= 4.151; p< .001; d de Cohen =.40), Generic Description (t(430)= 2.336; p< .05; d de Cohen =.23) and Assumption of Roles (t(430)= 3.582; p< .001; d de Cohen =.34) in favor of private schools. Finally, regarding the contact with people with disabilities, there are differences in the scale Personal Implication (t(430)= 2.585; p< .01; d de Cohen =.26) for people who have some contact. Conclusion: The findings provide the basis for proposals to optimize the attitudes, and empower those who are promoting the integration of people with disabilities.